Geminivirus Replication Protein impairs SUMO conjugation of PCNA at two acceptor sites. - Arroyo-Mateos, Manuel; Sabarit Penalosa, Blanca; Maio, Francesca; Sánchez-Durán, Miguel A.; Rosas-Díaz, Tábata Victoria; Prins, Marcel; Ruiz-Albert, Francisco Javier; Pérez-Luna, Ana Isabel; Van den Burg, Harrold; Rodríguez-Bejarano, Eduardo (ASM Journals, 2018)
Geminiviruses are DNA viruses that replicate in nuclei of infected plant cells using the plant DNA replication machinery, including PCNA (proliferating cellular nuclear antigen), a cofactor that orchestrates genome duplication and maintenance by recruiting crucial players to replication forks. These viruses encode a multifunctional protein, Rep, which is essential for viral replication, induces the accumulation of the host replication machinery, and interacts with several host proteins, including PCNA and the SUMO E2 conjugation enzyme (SCE1). Posttranslational modification of PCNA by ubiquitin or SUMO plays an essential role in the switching of PCNA between interacting partners during DNA metabolism processes (e.g., replication, recombination, and repair, etc.). In yeast, PCNA sumoylation has been associated with DNA repair involving homologous recombination (HR). Previously, we reported that ectopic Rep expression results in very specific changes in the sumoylation pattern of plant cells. In this work, we show, using a reconstituted sumoylation system in Escherichia coli, that tomato PCNA is sumoylated at two residues, K254 and K164, and that coexpression of the geminivirus protein Rep suppresses sumoylation at these lysines. Finally, we confirm that PCNA is sumoylated in planta and that Rep also interferes with PCNA sumoylation in plant cells
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/6221 https://journals.asm.org/author-self-archiving-permissions: "Authors may post their final published articles on their personal or university-hosted websites (e.g., institutional repositories, etc.), provided that a URL linking to the published article on the Journal's website appears and credit is given to the original ASM publication, preferably no earlier than 6 months after the final publication of the typeset article by ASM."
Keywords: Virus fitopatógenos - Genética; Geminivirus